Torrential bleed from lingual thyroid: an unusual cause of IUD - Bihani, Ameya; Dokhe, Yogesh; Hardikar, Priyanka; Dabholkar, Jyoti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Lingual thyroid is rare anomaly which results from failure of descent of thyroid gland to normal position in neck. The common mode of presentation is foreign body sensation, dyspnoea, dysphagia or rarely haemrrhage. Acute severe haemorrhage causes hypotensive shock which may lead to intra-uterine foetal distress or foetal death. We hereby present, a case of 22 year old primigravida who presented with massive oral haemorrhage secondary to hypertrophied lingual thyroid. Patient was successfully managed conservatively with oral thyroxine.